Exploring knowledge, awareness and perception of Clinical Physical Therapist toward Artificial intelligence application in Physical Therapy and Rehabilitation - Ikram ullah; Danish Mehmood; Dr. Sardar Alam; Hassan Khan; Saleem Malik; Fazal Rehman; Dr. Abdul Jalal khan PT; Malika Afzal; Wareesha Mahmood; Fida Hussain; Dr. Akbar Alam (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objectives:The study aimed to explore the knowledge, awareness and perception of Clinical Physical Therapist toward Artificial Intelligence application in Physical therapy and rehabilitation.Methods:Cross-sectional study was performed by distributing 5-point likert scale questionnaire among 117 physical therapists in Tertiary care hospitals in Peshawar.Results:On the basis of gender male physical therapist (49.15%), (54.23%) and (28.81%) have more knowledge as compare to female Physical therapist (18.96%), (18.96%) and (6.89). Males (27.1%), (28.81%) and (47.45%) were also aware more about AI applications then female (18.96%), (32.75%) and (17.24%). Increases knowledge and awareness amone also have high perception. On the basis of age categories 30-40years physical therapist have more knowledge and awareness than 20-30 years and 40-50years of physical Therapist also perception at different age categories were differ.Conclusion:AI is flattering further predominant and leading in clinical or health care and rehabilitation settings as an instrument or device it progress training patterns and patient conclusions. So, it is concluded on the basis of responses of clinical physiotherapist to the questionnaire that physical therapist have knowledge and awareness of artificial intelligence applications in field of physiotherapy and they have the perception if it is integrated in the field it can bring positive outcomes in management of patient condition.